Renin Inhibition by Aliskiren Protects Rats Against Isoproterenol Induced Myocardial Infarction - Khan, Vasim; Hassan, Md. Quamrul; Akhtar, Mohd.; Najmi, Abul Kalam (Drug Research, 2018)
Objective Cardioprotective potential of aliskiren against isoproterenol-induced myocardial infarction was evaluated in this study.Methods Wistar albino rats (n=36) were randomly divided into six groups. Normal control rats received 1 ml saline, orally for 14 days and 0.1 ml saline, subcutaneously on 13th and 14th treatment day while the toxic group animals were administered with saline orally for 14 days and isoproterenol (85 mg/kg, subcutaneously) on 13th and 14th day. In different pre-treatment groups, aliskiren (30, 50 & 100 mg/kg, orally) was administered for 14 days along with isoproterenol (85 mg/kg, subcutaneously) on the last two days. Per se group animals were given aliskiren (100 mg/kg orally) for 14 days. Twenty-four hours after the last drug treatment, cardiac marker enzymes (creatine kinase-MB and lactate dehydrogenase), apoptotic marker enzyme (caspase-3) and antioxidative enzymes (malondialdehyde, reduced glutathione, superoxide dismutase and catalase) were estimated, along with histopathological analysis of myocardium.Results Isoproterenol treatment caused a significant increase in cardiac markers, malondialdehyde, and caspase-3 levels with a considerable decrease in reduced glutathione, superoxide dismutase and catalase enzyme levels. Aliskiren at 50 and 100 mg/kg doses significantly alleviated the increase of caspase-3 and cardiac marker enzymes as well as the changes in antioxidant enzymes, which was confirmed by histopathological analysis. Aliskiren (100 mg/kg) produced more pronounced protective effects than its other two doses. Moreover, the changes in per se group were insignificant as compared to normal control group.Conclusion The present study thus provides an evidence for the protective effects of aliskiren in isoproterenol-induced myocardial infarction.